Prevalence and concentration of stx+ E. coli and E. coli O157 in bovine manure from Florida farms - Baker, Christopher A. (PLoS One, 2019)
Fresh produce outbreaks due to Shiga toxin-producing Escherichia coli (STEC) continue to occur in the United States (US). Manure-amended soils can pose a public health risk when used for growing raw agricultural commodities. Knowing the prevalence and concentration of STEC in untreated biological soil amendments of animal origin (BSAAO) is important to help guide the most appropriate pre-harvest interval(s) following application to limit risks from these soil amendments. Bovine manure samples were collected from 12 farms in Florida, including samples from piles, lagoons, barns, and screened solids. Two methods were used to detect stx1/2 and rfbE genes in samples. A prevalence rate of 9% for stx1 and/or stx2 and 19% for rfbE was observed from the 518 bovine manure samples evaluated. A most probable number (MPN) assay was performed on stx+ samples when applicable. The geometric mean for stx+ samples (n = 20) was 3.37 MPN g(-1) (0.53 log MPN g(-1)) with a maximum value of 6,800 MPN g(-1) (3.83 log MPN g(-1)). This research was part of a larger nationwide geographical study on the prevalence and concentration of STEC in bovine manure to help guide regulations on feasible pre-harvest intervals for the application of untreated BSAAO.